ADVL1522: A phase 2 study of lorvotuzumab mertansine (IMGN901) in children with relapsed or refractory wilms tumor, rhabdomyosarcoma, neuroblastoma, pleuropulmonary blastoma, malignant peripheral nerve sheath tumor, or synovial sarcoma—A Children's Oncology Group study. Issue 24 (11th September 2020) - Geller, James I.; Pressey, Joseph G.; Smith, Malcolm A.; Kudgus, Rachel A.; Cajaiba, Mariana; Reid, Joel M.; Hall, David; Barkauskas, Donald A.; Voss, Stephen D.; Cho, Steve Y.; Berg, Stacey L.; Dome, Jeffrey S.; et al.
Abstract : Background: Lorvotuzumab mertansine (IMGN901) is an antibody‐drug conjugate linking an antimitotic agent (DM1) to an anti‐CD56 antibody (lorvotuzumab). Preclinical efficacy has been noted in Wilms tumor, rhabdomyosarcoma, and neuroblastoma. Synovial sarcoma, malignant peripheral nerve sheath tumor (MPNST), and pleuropulmonary blastoma also express CD56. A phase 2 trial of lorvotuzumab mertansine was conducted to assess its efficacy, recommended phase 2 dose, and toxicities. Methods: Eligible patients had relapsed after or progressed on standard therapy for their tumor type. Lorvotuzumab mertansine (110 mg/m 2 per dose) was administered at the adult recommended phase 2 dose intravenously on days 1 and 8 of 21‐day cycles. Dexamethasone premedication was used. Pharmacokinetic samples, peripheral blood CD56‐positive cell counts, and tumor CD56 expression were assessed. Results: Sixty‐two patients enrolled. The median age was 14.3 years (range, 2.8‐29.9 years); 35 were male. Diagnoses included Wilms tumor (n = 17), rhabdomyosarcoma (n = 17), neuroblastoma (n = 12), synovial sarcoma (n = 10), MPNST (n = 5), and pleuropulmonary blastoma (n = 1). Five patients experienced 9 dose‐limiting toxicities: hyperglycemia (n = 1), colonic fistula (n = 1) with perforation (n = 1), nausea (n = 1) with vomiting (n = 1), increased alanine aminotransferase in cycle 1 (n = 2), and increased alanine aminotransferase in cycle 2 (n = 1) with increased aspartate aminotransferase (n = 1). Non–dose‐limiting toxicities (grade 3 or higher) attributed to lorvotuzumab mertansine were rare. The median values of the maximum concentration, half‐life, and area under the curve from zero to infinity for DM1 were 0.87 µg/mL, 35 hours, and 27.9 µg/mL h, respectively. Peripheral blood CD56+ leukocytes decreased by 71.9% on day 8. One patient with rhabdomyosarcoma had a partial response, and 1 patient with synovial sarcoma achieved a delayed complete response. Conclusions: Lorvotuzumab mertansine (110 mg/m 2 ) is tolerated in children at the adult recommended phase 2 dose; clinical activity is limited. Abstract : Lorvotuzumab mertansine is tolerated in children at the adult recommended phase 2 dose. Clinical activity is limited against targeted tumors.